Selective Reaching: Distracter Effects on Movement Kinematics as a Function of Target-Distracter Separation. - Keulen, Ron F.; Adam, Jos J.; Fischer, Martin H. (Journal of General Psychology, 2004)
The authors investigated distracter effects on the kinematics of reaching movements to determine when during reaching responses (reaction time, time to peak velocity, time after peak velocity, or peak velocity) distracter interference occurred and how target-distracter separation affected the locus of interference. Participants moved a pen on a digitizing tablet toward a target appearing with or without a distracter. With a small target-distracter separation, distracter interference occurred during time after peak velocity (similar amounts of interference from near and far distracters). With a large target-distracter separation, distracter interference occurred during time to peak velocity (more interference from near compared to far distracters). The results demonstrated that target-distracter separation is an important determinant of the locus of distracter interference. Reprinted by permission of the publisher.